Prevalence of hearing loss in college students: a meta-analysis - Kornisch, Myriam; Barton, Ashley; Park, Hyejin; Lowe, Rebecca; Ikuta, Toshikazu (Frontiers in Neuroscience, 2024)
Hearing loss among college students, specifically noise-induced hearing loss (NIHL), appears to be increasing. This may be particularly challenging for this population as college students are required to listen to lectures in classrooms that may have suboptimal listening environments. College-aged musicians are at a particularly high risk due to repeated and extended exposure to loud noise. Therefore, the purpose of the current study was (1) to examine the prevalence of hearing loss in college students and (2) to emphasize the importance of detecting hearing loss at 6,000 Hz.A meta-analysis was conducted using the PRISMA model. The literature search yielded 8 studies (1,950 subjects) that tested hearing loss using an audiogram and Distortion Product Otoacoustic Emissions (DPOAEs). All studies used audiologic tests to detect hearing loss among college students between the ages of 17-35 years.Results indicate that the prevalence of hearing loss in college students is 19%. In addition, the prevalence of hearing loss at 6,000 Hz is 85% among student musicians. For this meta-analysis, slight sensorineural hearing loss, or thresholds greater than 20 dB bilaterally or unilaterally, qualified as hearing loss.Discussion: Decreased hearing at 6,000 Hz may lead to an individual's inability to hear important environmental factors and high frequency speech sounds. College students without full auditory function at this frequency may have difficulties performing in class based on decreased attention, comprehension, and memory. Although students may not realize the influence of their 6,000 Hz hearing loss or be unaware of its presence, it could significantly change their likelihood to succeed in college. Therefore, implementing a hearing conservation program may be advised for colleges and universities to help prevent hearing loss in students, particularly for collegiate musicians. In addition, it may be beneficial to screen hearing in college students at 6,000 Hz for better detection of hearing loss overall.